The Importance of Personal Protective Equipment in Firefighter Safety and Health Efforts in the North Nias District Fire and Rescue Field: - Nazara, Delnovi Yanti; Mendrofa, Martha Surya Dinata; Telaumbanua, Eliagus; Harefa, Idarni (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
Personal protective equipment (PPE) refers to gear utilized to safeguard individuals from hazards, accidents, and work-related illnesses. It is typically employed in environments where there is a heightened risk of harm to workers and those around them. This equipment encompasses garments and accessories designed to shield workers from hazardous substances, processes, machinery/tools, facilities, and surroundings, thereby reducing the likelihood of accidents and illnesses. PPE should be comfortable to wear and should not impede work in order to provide effective protection. Its primary objective is to prevent work-related diseases. The use of PPE is not limited to workers alone but extends to anyone entering and interacting with the work environment. PPE is intertwined with occupational safety and health (OSH) because it contributes to maintaining OSH standards. OSH, as mandated by labor laws, revolves around ensuring the physical and mental well-being of the workforce, with a focus on accident and illness prevention and management in the workplace.